Anti‐KIT monoclonal antibody CDX‐0159 induces profound and durable mast cell suppression in a healthy volunteer study. Issue 8 (3rd March 2022) - Alvarado, Diego; Maurer, Marcus; Gedrich, Richard; Seibel, Scott B.; Murphy, Michael B.; Crew, Linda; Goldstein, Joel; Crocker, Andrea; Vitale, Laura A.; Morani, Pamela A.; Thomas, Lawrence J.; Hawthorne, Thomas R.; et al.
Abstract: Background: Mast cells (MC) are powerful inflammatory immune sentinel cells that drive numerous allergic, inflammatory, and pruritic disorders when activated. MC‐targeted therapies are approved in several disorders, yet many patients have limited benefit suggesting the need for approaches that more broadly inhibit MC activity. MCs require the KIT receptor and its ligand stem cell factor (SCF) for differentiation, maturation, and survival. Here we describe CDX‐0159, an anti‐KIT monoclonal antibody that potently suppresses MCs in human healthy volunteers. Methods: CDX‐0159‐mediated KIT inhibition was tested in vitro using KIT‐expressing immortalized cells and primary human mast cells. CDX‐0159 safety and pharmacokinetics were evaluated in a 13‐week good laboratory practice (GLP)‐compliant cynomolgus macaque study. A single ascending dose (0.3, 1, 3, and 9 mg/kg), double‐blinded placebo‐controlled phase 1a human healthy volunteer study ( n  = 32) was conducted to evaluate the safety, pharmacokinetics, and pharmacodynamics of CDX‐0159. Results: CDX‐0159 inhibits SCF‐dependent KIT activation in vitro . Fc modifications in CDX‐0159 led to elimination of effector function and reduced serum clearance. In cynomolgus macaques, multiple high doses were safely administered without a significant impact on hematology, a potential concern for KIT inhibitors. A single dose of CDX‐0159 in healthy human subjects was generally well tolerated and demonstrated long antibody exposure. Importantly, CDX‐0159 led to dose‐dependent, profound suppression of plasma tryptase, a MC‐specific protease associated with tissue MC burden, indicative of systemic MC suppression or ablation. Conclusion: CDX‐0159 administration leads to systemic mast cell ablation and may represent a safe and novel approach to treat mast cell‐driven disorders. Abstract : This study presents the preclinical characterization, safety, pharmacokinetic and pharmacodynamic activity in a placebo‐controlled phase 1a healthy volunteer study of CDX‐0159, a specific and potent anti‐KIT inhibitory monoclonal antibody. CDX‐0159 inhibits SCF‐dependent KIT and mast cell activation. In a dose‐dependent manner, CDX‐0159 induces suppression of plasma tryptase – a marker of mast cell burden – showing a potential as a therapeutic strategy in mast cell‐driven disorders.Abbreviations: CDX‐0159, anti‐KIT inhibitory monoclonal antibody; FcR, Fc receptor; KIT, KIT proto‐oncogene, receptor tyrosine kinase; MRGPRX2, mas‐related G protein‐coupled receptor‐X2; SCF, stem cell factor